Adaptive and concurrent negotiation for an efficient cloud provisioning. (18th March 2020) - Omezzine, Aya; Saoud, Narjes Bellamine Ben; Tazi, Said; Cooperman, Gene
With the growth of competitiveness in the cloud, business providers must ensure efficient provisioning which maximises the customer satisfaction and optimises their profit. Efficient cloud provisioning that satisfies the end users and maximises the providers' profit becomes harder when considering inflexible take-it-or-leave-it SLAs. Negotiation-based approaches are promising solutions when dealing with conflicts. Using negotiation, the users and the providers may find a satisfactory agreement. However, reaching a compromise between the two parties is a cumbersome task due to the workload constraints at negotiation time. In terms of solutions, the majority of the approaches in the literature propose to reject the users' requests when the negotiation fails. In this paper, we propose a novel adaptive negotiation approach that concurrently renegotiates with all of the users when the workload changes. Experiments show that this approach maximises the business provider's profit, increases the number of accepted users, and improves the customer satisfaction.